Periodismo ambiental en los portales de El Universo y El Comercio. - Bautista Tocto, Johanna Carolina (2016)
Environmental information in websites is a social, economic, political and cultural issue of interest for its global influence, due to issues such as: the dramatic population growth, replacement of green open spaces for the expansion of cities, over-exploitation of natural resources, the outbreak of epidemics, the ferocity of natural disasters, pollution and other causes for the environmental imbalance are elements to make society aware and to take right decisions about choosing their local and national governments to build the Good Living, which is the base of the Ecuadorian Constitution proposing a way of life in which nature and humans live in harmony. Following this intention, the purpose to analyze the characteristics of the way newspapers as El Universo and El Comercio expose news related to the environment through its Internet portals, in order to determine the most distinctive features, the potential and / or limitations of ambiental journalism. This research declares with the outset, a summary of the historical development of climate-related problems conditioned by human initiatives and actions and the development of environmental journalism. This present research sets on the outset, a sinthesis of the historical and journalism development of the environmental issues related to the climate that human beings are envolved with actions, and the differences - similarities about concepts of Investigative Journalism, scientifice journalism, Environmental Journalism, environmental information and Digital journalism to reveal the role of environmental journalists. Finally, the analysis results about environmental topics will be exposed in publications from january to march 2015 within the portals of the analyzed media.